Model predicts compositional grading of a reservoir in Iran - JAMSHIDNEZHAD, Mohammad; FARAZMAND, Mohammad (The Oil & gas journal, 2005)
A study showed that an isothermal gravity-chemical equilibrium model can predict the compositional variation with depth for the Asmari carbonate reservoir in Marun field, Iran. The basis of the study was laboratory pressure-volume-temperature (PVT) reports on 15 appraisal wells. The study involved the calibration of the equation of state (EOS) for compositional simulation and established a means for predicting fluid properties for the entire area of the field. In the study, a three-parameter Peng-Robinson equation of state was used to match all laboratory PVT data from the Asmari reservoir. This step was followed by a regression technique with dynamic parameter selection for tuning the EOS. This study uses a balance of driving forces or flux equations to satisfy the condition of zero component net flux. In this reservoir, a temperature differences are small with respect to the absolute reservoir temperature, and one may expect that an equilibrium model will give an adequate fluid composition and properties description.